Modern Big Data Processing with Hadoop : Expert techniques for architecting end-to-end big data solutions to get valuable insights /: Expert techniques for architecting end-to-end big data solutions to get valuable insights. (2018) - Kumar, V Naresh; Shindgikar, Prashant
No abstract available